Democratic Representation and Legislative Theatre. Issue 164 (1st September 2020) - Dalaqua, Gustavo H.
Abstract: This article seeks to contribute to the debate on how political representation can promote democracy by analysing the Chamber in the Square, which is a component of legislative theatre. A set of techniques devised to democratise representative governments, legislative theatre was created by Augusto Boal when he was elected a political representative in 1993. After briefly reviewing Nadia Urbinati's understanding of democratic representation as a diarchy of will and judgement, I partially endorse Hélène Landemore's criticism and contend that if representation is to be democratic, citizens' exchange of opinions in the public sphere should be invested with the power not only to judge but also to decide political affairs. By opening up a space where the represented can judge, decide, and contest the general terms of the bills representatives present in the assembly, the Chamber in the Square harnesses political representation to democracy.